V.1 - "Ray, Arun" (New Delhi, 2004)
This book provides a historical perspective of the conceptual evolution of human rights and the institutional underpinning for the protection of the rights of citizens in contemporary Indian politics. Within this larger framework, The study focuses on the role of the National human rights Commission of India since its origin. The book critically examines the following topics: human rights in theoretical perspective establishment, structure and status of the National human rights Commission.
Keywords: Human rights-India